Removal of acrylic acid from process water by using activated carbon based coconut shell - Nor Rashidah, Ahmed (2012)
The presence of Acrylic Acid (AA) in process water is the major problem in many industries which are using AA.There are no proper methods available to remove AA from process water and hence the industries incinerating the process water containing AA to remove it.This method consumes large amount of natural gas and in turn leads to high energy consumption.This research attempt to remove AA via batch adsorption process by using activated carbon based coconut shell.The process water that taken from BASF Petronas Chemicals Sdn Bhd containing 4 wt % of AA is used as sample water in this study.The adsorption capacity was tested by varying different size of activated carbon (granular and powder)amount of activated carbon and contact time.The initial and final concentration of AA was tested by using High performance liquid chromatography (HPLC).The performance of adsorption process is modeled using three types of adsorption isotherms namely,Langmuir isotherms, Freundlich isotherm and Redlich-peterson isotherm.From the experimental results it was found that the activated carbon based coconut shell was good in removing AA from process water and Langmuir isotherm describe the process well compared to other two isotherms with value R2 = 0.94278 %. The maximum capacity of adsorption by using activated carbon based coconut shell was found, qm = 94.3396 mg/g with the dosage used of 400 g/L.In addition to that,the adsorption of acrylic acid onto powder activated carbon represents the favorable process.